Measuring User Experience of Blended Learning Application: A Case Study of Higher Education - Abdul Rahim R.; Kalaichelven J.; Ibrahim R. (Association for Computing Machinery, 2023)
Computer aided instruction; E-learning; Students; And malaysia; Blended learning; Case-studies; Delivery methods; High educations; Learning modules; Malaysia; Post-graduate levels; Student engagement; Users' experiences; Efficiency